Improvement in quality of handmade paper materials by recycling of waste papers and PPE kits. (2021) - Kumar, Vijay; Gupta, Shipra; Kalra, J.S.; Patil, P.P.
Abstract: In this pandemic, the requirements of PPE kits are increasing continuously. The doctors and health care workers are using the kits to protect themselves from the virus. After using, these kits become waste. The consumption of these kits becomes a very big challenge for the municipal corporation. Similarly, the papers which are used in offices become waste after use. The consumption of these papers is also a challenge as in the garbage of a city, the maximum percentage is available in the form of waste papers. The waste papers may be recycled after some recycling process and manufacture handmade papers. The quality of handmade papers will be not as good as traditional papers. By the use of waste medical PPE kits and pulp of used office papers, the quality of handmade papers may be increased. Recycling of used papers and medical PPE kits are also useful for the environment and forests. In this manuscript, it is seen that the combined pulp of waste papers and medical PPE kits in the various ratios may increase or decrease the hardness strength, reflection properties, and moisture properties of handmade papers.